Vapor/gas separation through carbon molecular sieve membranes: Experimental and theoretical investigation. (8th March 2022) - Poto, Serena; Endepoel, Joost G.H.; Llosa-Tanco, Margot Anabell; Pacheco-Tanaka, David Alfredo; Gallucci, Fausto; Neira d'Angelo, M. Fernanda
Abstract: The separation of H2 O vapor from (hydrogen-rich) gaseous streams is a topic of increasing interest in the context of CO2 valorisation, where the in situ water removal increases product yield and catalyst stability. In this work, composite alumina carbon molecular sieve membranes (Al-CMSM) were prepared from phenolic resin solutions loaded with hydrophilic boehmite (γ-AlO(OH)) nanosheets (0.4–1.4 wt. % in solution) which partially transform to γ-Al2 O3 nanosheets upon thermal decomposition of the resin, improving the hydrophilicity and thus the adsorption-diffusion contribution of the H2 O permeation. The γ-Al2 O3 nanosheets showed no influence on the pore size distribution of the membranes in the range of micropores, but they increased the membrane hydrophilicity. In addition, the use of boehmite in the resin solution causes an increase in the viscosity and thus an increase in the carbon layers thickness deposited on the porous α-Al2 O3 support (from 1 to 3.3 μm). Furthermore, the alumina sheets introduce defects in the carbon matrix, increasing the tortuosity of the active layer, as concluded via phenomenological modelling and parametric fitting of the experimental results. As a consequence, the water permeability exhibits a maximum (1.3ꞏ10 −6  molꞏs −1 Pa −1 m −1 at 150 °C) with boehmite/alumina content of ca. 0.8 wt. %, as the combined effects of increasing hydrophilicity (which favour H2 O permeability) and increasing thickness and tortuosity (which hamper permeability) upon increasing boehmite loading. Similarly, the H2 O/gas perm-selectivity is optimum at 1.2 wt. % boehmite loading. We further investigated the H2 O permeation mechanism by modelling the mono- and multi-layer adsorption and capillary condensation of water in microporous media, which result as the main transport mechanisms in the explored conditions. Highlights: Several boehmite-phenolic resin composite carbon molecular sieve membranes were developed. The hydrophilic boehmite nanosheets were used to increase the adsorption of water. Water permeability shows an optimum with the initial boehmite content around 0.8 wt. %. CMSM are promising material for the water separation from gaseous mixtures at relatively high temperatures.